The future of work in the era of emerging technologies - Palazzani, Laura (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
There are three main intersections between transhumanism and the future of work, related to the different meanings of transhumanism: 1. the radical meaning of the transformation of the human condition towards perfection beyond humanity conceived as a limitation (technologization of the body and artificialization of the mind through robotics and artificial intelligence (AI)) in the context of the devaluation of the human being1: towards perfection «beyond» the human range in the workplace; 2. the intermediate meaning of enhancement as the quantitative and qualitative increase of human capacities (physical, mental, emotional)2: towards perfection «in» humans in the workplace; 3. the use of emerging technologies (as the most recent fast and complex advancement of technologies)3 in order to enhance «human work».
Keywords: transhumanism; work; emerging technologies